BRONKOPNEUMONIA ON PEDIATRIC PATIENT - Andy Samuel (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Bronkhopneumonia is still disease with a wide spectrum of clinical presentation often with unpredictable clinical progression andoutcome. It is often difficult to predict the subset of patients who will progress from non-severe to severe disease. A 6 years old boyadmitted to the hospital for his acute fever for three days accompanied with shortness of breath. He also complained cough with pleghm, headache, nausea, and vomitting. There was rash on his limbs and his gums bleed several hours ago. He looks ill, compos mentis, temperature was 38.9°C, pulse was regular 112 x/min, respiration rate was 24 x/min, there was cyanosis, nostril breath (+), and found ronchi on auscultation. Blood workup showed thrombocytosis and increasing LED with no leukocytosis. He was diagnosed with bronkhopneumonia and then he received intravenous fluid, oxygen, i.v line broadspectrum antibiotic, andacetaminophen. Bronkhopneumonia has many cause of disease so it should receive more attention to symptoms and signs to get information of the severity of the disease. The most important treatment for bronkhopneumonia patient is symptomative therapy. [J Agromed Unila 2014; 1(2):185-189]Keywords: bronkhopneumonia, thrombocytosis, virus